Fundamental design features - Hackshaw, Allan (Henry Stewart Talks, 2025)
Population, Intervention, Control, Outcomes (PICO), Trial randomisation, Trial study size, Trial follow-up and data collection, Placebo, Unblinded, single- and double-blinded trials